Expression of Building Form Based on Neo Vernacular Architecture in the Design of Wuna Trade Center in Raha, Muna Regency - Fuad Afllal Mahfudh; Sigit Hadi Laksono (Journal of Civil Engineering, Planning and Design, 2026)
The development of modern trade centers in urban areas requires a design approach that is not only functional but also able to express local identity. This study examines the building form approach in the design of the Wuna Trade Centre in Raha, Muna Regency, with the theme of Neo Vernacular Architecture. The design methodology is carried out through literature studies, observations of traditional Muna architecture, and analysis of form transformations during the design stage. The design results show that the adopted building mass form reflects the character of the Muna traditional house through a reinterpretation of the gable roof shape, the use of large columns (pilotis), and a façade with local woven motifs. The form transformation is carried out in four stages, form the basic rectangular mass to the formation of a commercial silhouette with local characteristics. This approach not only strengthens the visual image of the building as a city landmark but also creates a cultural relationship between architecture and local community. This study confirms that building from can be a medium for cultural preservation within the framework of adaptive and contextual contemporary design.